2001
DOI: 10.1046/j.1525-1594.2001.025001022.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Kinematic Analysis of Total Knee Arthroplasty with Four Different Polyethylene Designs

Abstract: The femorotibial contact point on the sagittal plane was measured under weight-bearing conditions in 45 subjects with implanted and nonimplanted knees. They consisted of 11 knees with flat bearing inserts, 16 knees with shallow dished inserts, 10 knees with posterior lipped inserts, 10 knees with posterior stabilized bearing inserts, and 8 normal knees selected as controls. The average amount of anterior translation of the knee with a flat bearing insert was significantly larger than that of the other implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Indeed, many studies have shown a paradoxical slide‐forward of the tibiofemoral contact point with increasing flexion and enormous interindividual differences in the kinematic pattern, especially in posterior cruciate retaining prostheses. [1–3, 8–10, 15–17, 25, 31, 39, 40, 43, 44]. This pattern was found in fixed‐ and mobile‐bearing prostheses.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, many studies have shown a paradoxical slide‐forward of the tibiofemoral contact point with increasing flexion and enormous interindividual differences in the kinematic pattern, especially in posterior cruciate retaining prostheses. [1–3, 8–10, 15–17, 25, 31, 39, 40, 43, 44]. This pattern was found in fixed‐ and mobile‐bearing prostheses.…”
Section: Discussionmentioning
confidence: 82%
“…This pattern was found in fixed‐ and mobile‐bearing prostheses. Only posterior stabilized prostheses had less variations in deep flexion and during gait [2, 8, 10, 16, 17, 31, 32, 35, 43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the kinematic performance of PS TKR designs (Wada et al 2001;Banks and Hodge 2004;Haas et al 2002;Kanekasu et al 2004;Argenson et al 2005;Yamazaki et al 2005) report observing femoral rollback. Fantozzi et al (2006) correlated significantly higher clinical and functional scores with a more posterior condylar position.…”
Section: Introductionmentioning
confidence: 99%
“…The ligament tension and geometry of the polyethylene insert may influence the AP laxity with less tension of the ligaments creating more AP laxity [14]. A more dished insert means more congruency with the femoral component, leading to less AP laxity in the knee.…”
Section: Introductionmentioning
confidence: 99%